2020
DOI: 10.1177/0004867420937806
|View full text |Cite
|
Sign up to set email alerts
|

The response to COVID-19 in prisons must consider the broader mental health impacts for people in prison

Abstract: Therefore, brexpiprazole might induce mild sedation, mild extrapyramidal signs and mood stabilization. Overall, brexpiprazole may be a therapeutic option to alleviate BPSD in patients with VD in the oldest old. Declaration of Conflicting Interests The author(s) declared no potential conflicts of interest with respect to the research, authorship and/or publication of this article. Patient Consent After explaining the study to the patient and caregivers, written informed consent was obtained. This study was appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 5 publications
1
20
0
1
Order By: Relevance
“…Other research themes identified include eating disorders, in particular, the re‐examination of diagnostic criteria (Hay, 2019; Phillipou & Beilharz, 2019); an examination of Australia's primary mental health “Better Access” program (Judd & Davis, 2019; Rosenberg & Hickie Am, 2019); the impact of COVID‐19 on vulnerable groups (Maguire & Looi, 2020; Page, Sperandei, Spittal, & Pirkis, 2020; Stewart, Cossar, & Stoové, 2020), mental health systems (E. J. Tan, Meyer, et al, 2020), and the rapid expansion of telehealth (Khanna & Forbes, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Other research themes identified include eating disorders, in particular, the re‐examination of diagnostic criteria (Hay, 2019; Phillipou & Beilharz, 2019); an examination of Australia's primary mental health “Better Access” program (Judd & Davis, 2019; Rosenberg & Hickie Am, 2019); the impact of COVID‐19 on vulnerable groups (Maguire & Looi, 2020; Page, Sperandei, Spittal, & Pirkis, 2020; Stewart, Cossar, & Stoové, 2020), mental health systems (E. J. Tan, Meyer, et al, 2020), and the rapid expansion of telehealth (Khanna & Forbes, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…35 43 47 70 73-78 Many were concerned that isolation may lead to exacerbations of mental health conditions, anger, depression, psychosis, self-harm and suicide. 39 46 56 66 72 74-76 [79][80][81][82][83][84] There were also concerns that isolation in JCFs will affect young offenders' neurological development. 63 74 85 In this context, it is important to clarify the difference between isolation and solitary confinement.…”
Section: Fear Of Covid-19mentioning
confidence: 99%
“…1 3 Included studies did not address the potential harms associated with prolonged infection control strategies, such as isolation and physical distancing. 88 This may particularly affect the mental health of PIP, who have higher background of mental illness than community peers 89 and the detrimental effects of solitary confinement in correctional facilities on mental health need to be carefully weighed up, 90 including potentially elevating risk of self-harm. Therefore, mental health should be at the forefront of considerations when implementing infection control measures in prisons to mitigate adverse consequences for PIP.…”
Section: Research Gapsmentioning
confidence: 99%